Pemanfaatan Biogas Dari Limbah Kotoran Sapi Sebagai Alternatif LPG Di Desa Gantiwarno, Lampung Timur - Rihardian Maulana Wicaksono; Muhammad Rizky Zen; Ilham Dwi Arirohman; Khoirun Naimah; Agung Dwi Saputra; Muhammad Ridho Hilman (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Gantiwarno Village in Pekalongan, East Lampung, has significant biogas potential from cow dung. However, the utilization of cow dung is still not optimal, resulting in the surrounding environment being littered with cow dung. Furthermore, the availability of LPG is uncertain, causing its price to fluctuate. Therefore, ITERA Community Service team helped resolve this issue by installing a 4 m3 biogas reactor to convert cow dung into biogas. The stages of this Community Service activity began with a site survey, building relationships with partners, team preparation, construction of the biogas installation, monitoring and evaluation of activities, and the preparation of activity reports. The output of this community service activity was a biogas reactor unit and supporting components such as a biogas stove. Within 7-10 days, the biogas from the cow dung waste began to appear and was immediately used for household cooking needs. Visually, the flame in the biogas stove showed a blue color, indicating that the quality of biogas was not much different from the LPG gas used previously. This biogas reactor can be a renewable, environmentally friendly energy source, making it more energy independent. Furthermore, utilizing biogas can help reduce dependence on LPG, thus saving on weekly electricity needs.